HOW SOIL CHARACTERISTICS AND WATER QUALITY INFLUENCE THE BIOGEOCHEMICAL RESPONSE TO FLOODING IN RIVERINE WETLANDS - Loeb R.; Van daalen E.; Lamers L.P.M.; Roelofs Ja.G.M. (My University, 2007)
Although phosphate concentrations have been reduced, the rivers Meuse and Rhine are still polluted with sulphate, which most probably affects vegetation development in newly created riverine wetlands. The influence of flooding with river water rich in sulphate was tested on three soil types from floodplains of the river Meuse using flow-through and batch experiments. Soils were selected for contrasting concentrations of iron and organic matter and originated from a floating fen (iron-poor, organic), an alder carr (iron-rich, organic) and a clay pit (iron-rich, low in organic matter). Flooding induced mobilisation of phosphate. Sulphate only enhanced this effect in the alder carr soil, where sulphide and phosphate competed for binding to iron. Only in the floating fen soil did the addition of sulphate result in the formation of free sulphide, which reduced the growth of Glyceria maxima, serving as a phytometer. In addition, the floating soil started to sink, due to falling methane concentrations. In the different soil types methane production was hampered by the presence of more favourable electron acceptors such as sulphate in the water and Fe(III) in the soil. It was concluded that the effects of inundation with sulphate-polluted water strongly depend on the soil type: under iron-poor circumstances, free sulphide may accumulate, leading to phytotoxicity, while in soils rich in iron, sulphide toxicity is prevented, but phosphate availability may be increased. In addition, shortage of easily degradable organic matter can limit the formation of potential toxicants such as ammonium, iron and sulphide. Results are discussed in terms of their implications for nature management.
Keywords: BUOYANCY; EUTROPHICATION; FLOODING; FLOODPLAIN; METHANE; SULPHATE; WATER STORAGE